The Effect of Storytelling Intervention on the Mental Health of Preschool Children - Chatarina Suryaningsih; Nadyah Faadhillah Husain (Journal of Public Health Sciences, 2026)
Every year, around 24.6% of children aged 0-17 years in the world experience mental health problems. One of the efforts to improve mental health is the introduction of reading from an early age through storytelling. The purpose of this study is to analyze the effect of storytelling intervention on mental health in preschool children. This research uses a Quasi-experimental design through the Nonequivalent Control Group Design approach. Sampling used the total sampling technique with a total of 61 children enrolled in Kartika VIII-42 Cimahi Kindergarten. Data were obtained using the Strength Difficulties Questionnaire. The tests used were the dependent t-test and the independent t-test. The results of the study were obtained in the intervention group; the mean before the intervention was 8.88 and the mean after the intervention was 6.69. In the control group, the mean before the intervention was 10.41 and the mean after the intervention was 10.69. The results of the independent t-test obtained a p-value after intervention in both groups of 0.002 (α < 0.05); there was a difference in mental health after intervention in the intervention group and the control group. It is hoped that storytelling will be used as a promotional effort in improving children's mental health, and the school will make storytelling activities a routine activity in helping children to improve their mental health from an early age.